The effect of spiritual intelligence and self-control on nomophobia in Islamic Education Students at Muhammadiyah University - Syafiqoh, Salwa Salsabila; Sari, Ratna (Jurnal Psikologi Terapan dan Pendidikan, 2025)
Nomophobia, the fear of being without a smartphone, is increasingly prevalent among university students and may be influenced by psychological factors such as spiritual intelligence and self-control. Several studies have demonstrated that these psychological factors play a significant role in nomophobic tendencies among college students. This quantitative study employs multiple regression analysis to examine the influence of spiritual intelligence and self-control on nomophobia in a sample of 99 Islamic Education students at Muhammadiyah University of Yogyakarta, selected through simple random sampling. Data were collected using validated instruments the NoMoPhobia Questionnaire (NMP-Q), the Spiritual Intelligence Self-Report Inventory, and a self-control self-report scale. Data analysis included descriptive statistics, classical assumption tests, and multiple linear regression using SPSS version 26. Descriptive analysis revealed that 67.68% of students exhibited high spiritual intelligence, 67.67% demonstrated moderate self-control, and 92.92% experienced high levels of nomophobia. Multiple regression analysis revealed that spiritual intelligence had a significant positive effect on nomophobia (β=0.277, p=0.004), whereas self-control had a significant negative effect (β=-1.015, p<0.001). The model explained 67% of the variance in nomophobia (R²=0.670, Adjusted R²=0.663), indicating a strong influence. However, the R² value of 0.276 mentioned elsewhere suggests moderate explanatory power, which may require clarification. Both spiritual intelligence and self-control significantly affected nomophobia among university students. These findings underscore the importance of developing spiritual intelligence and self-control to reduce nomophobia levels in this population.